Serial test is superior to the traditional sequences random tests - YU Yi-zhou1; OU Hai-wen 1 (Tongxin xuebao)
Random sequences play an important role in cryptographic research.NIST publishes 16 standard tests in March,2001 to test the randomness of binary sequences.Serial test is included in the 16 tests but the traditional ordered-pair test and poker test are not.Serial test was analyzed to be superior to the other two tests even when they are used together.So it can replace them and be selected by NIST.